Maternal plasma perfluoroalkyl substances concentrations in early pregnancy and cardiovascular development in offspring: A prospective cohort study. (March 2023) - Wang, Jian; Du, Bowen; Wu, Yujian; Li, Zhuoyan; Wang, Hualin; Niu, Yiwei; Ye, Yujiao; Chen, Qian; Wang, Qianchuo; Wu, Yurong; Chen, Sun; Zhang, Xi; et al.
Highlights: Maternal plasma PFAS levels are associated with cardiovascular development in children. Short-chain PFAS levels are associated with decreased cardiac wall thickness. Long-chain PFAS levels are associated with decreased vascular wall thickness. Abstract: Background: High maternal plasma perfluoroalkyl substances (PFAS) concentrations has been associated with adverse birth outcomes, but data on early childhood cardiovascular health is limited. This study aimed to assess the potential association between maternal plasma PFAS concentrations during early pregnancy and cardiovascular development in offspring. Material and methods: Cardiovascular development was assessed through blood pressure measurement, echocardiography and carotid ultrasound examinations among 957 children from the Shanghai Birth Cohort aged at 4 years old. Maternal plasma concentrations of PFAS were measured at mean gestational age of 14.4 (SD:1.8) weeks. The joint associations between PFAS mixture concentrations and cardiovascular parameters were analyzed using a Bayesian kernel machine regression (BKMR). The potential association of individual PFAS chemicals concentrations was explored using multiple linear regression. Results: In BKMR analyses, carotid intima media thickness (cIMT), interventricular septum thickness in diastole and systole, posterior wall thicknesses in diastole and systole, and relative wall thickness were significantly lower when all log10-transformed PFAS were fixed at 75th percentile in comparison to at their 50th percentile[Estimated overall Risk:-0.31 (95%CI: −0.42, −0.20), −0.09 (95%CI: −0.11, −0.07), −0.21 (95%CI: −0.26, −0.16), −0.09 (95%CI: −0.11, −0.07), −0.07 (95%CI: −0.10, −0.04) and −0.005 (95%CI: −0.006, −0.004)].Furthermore, maternal plasma concentrations of individual short-chain PFAS was associated with a decrease in left ventricular wall thickness, intraventricular septum thickness and enlarged chamber volume, and long-chain with a decrease in cIMT. Conclusions: Our findings suggest that maternal plasma PFAS concentrations during early pregnancy was adversely associated with cardiovascular development in offspring, including thinner cardiac wall thickness and cIMT.